(untitled) (Global Psychiatry Archives, 2026)
Introduction: Hypertension is a prevalent condition and tobacco usage is a known risk factor for its development. The Brief Intervention is a targeted and time-limited approach that aims to promote behavior change and improve health outcomes. The aim of the present study was to determine the effectiveness of Brief Interventions on readiness to change and treatment initiation in hypertensive patients who use tobacco. Method: An experimental study was conducted on 80 adult patients with hypertension who were tobacco users and seeking treatment at Department of Cardiology in a tertiary care hospital. Data was collected through structured and semi structured questionnaires i.e. socio-demographic and clinical variables, the ASSIST and a readiness to change questionnaire. Result: The majority of patients were male, married, and living in urban areas. Tobacco use was prevalent among the patients, with 77.5% using smokeless tobacco. Before the interventions, the majority (87.5%) were in the contemplation phase, 10% were in the action phase, and only 2.5% were in the maintenance phase whereas after interventions the majority (80%) was still in the contemplation phase, 15% had progressed to the action phase, and only 5% were in the maintenance phase for readiness to change. Conclusion: The present study revealed that Brief Intervention proved effective in enhancing readiness for change in patients with hypertension using tobacco. The mean score post intervention (110.20) was higher than the pre interventional score (97.41), indicating an increase in readiness for change after the brief intervention. There is a significant difference between before and after intervention with the t-value of 13.58 with 79 degrees of freedom & p value of < 0.001 which was statistically significant at the .05 level.